دور الاتصال الرسمي في تحفيز المورد البشري دراسة ميدانية بالمؤسسة المينائية- بسكيكدة - بن موسى (My University, 2019)
Abstract: the study aimed to identify the role of official communication in stimulating the human resource within the institution, whether ascending, descending or horizontal in motivating employees, especially moral motivation, such as letters of thanks and praise, participate in taking Resolution, upgrade, training, and configuration...etc A field study was conducted at the Port institution of SKIKDA. The central question of the current study from the outset was "what is the role of official communication in motivating the human resource within the port institution?" The current area of study was the "Port institution of SKIKDA as a model for the Algerian Foundation, which has undergone a process of equilibrium with the economic growth of the Algerian society as a whole, and its implications for the way of communication and its relationship to motivation within the institution. In our study we relied on the descriptive approach, which relies on the collection of data on the phenomenon and its interpretation in the analysis of the form, as for the sample, we applied in our study this proportional class sample, which represents the number of its members in 105 vocabulary we have distributed the form to them, while 95 were recuperated from Total distributed. The results of the study concluded that the official communication has a major role in motivating the employees in this institution as it pushes them to perform better tasks, and allows official communication to express their concerns and interests by listening to them and participating in decision making, as well as paying attention to the worker from the moral standpoint of in directing, developing his abilities and skills and creating a sense of belonging to his institution, all this would lead to the achievement of the objectives of the institution. --------------------------- ملخص: هدفت الدراسة إلى تحديد دور الاتصال الرسمي في تحفيز الموارد البشرية داخل المؤسسة، سواءً كان تصاعديًا أو تنازليًا أو أفقيًا، في تحفيز الموظفين، لا سيما التحفيز المعنوي، كرسائل الشكر والثناء، والمشاركة في اتخاذ القرارات، والترقية، والتدريب، والتكوين... إلخ. أُجريت دراسة ميدانية في المؤسسة المينائية بسكيكدة. وكان السؤال المحوري للدراسة منذ البداية هو: "ما دور الاتصال الرسمي في تحفيز الموارد البشرية داخل المؤسسة المينائية؟" مجال الدراسة الحالي هو "مؤسسة ميناء سكيكدة" كنموذج للمؤسسة الجزائرية، التي شهدت عملية توازن مع النمو الاقتصادي للمجتمع الجزائري ككل، وانعكاساته على أسلوب الاتصال وعلاقته بالتحفيز داخل المؤسسة. اعتمدنا في دراستنا على المنهج الوصفي، الذي يعتمد على جمع البيانات حول الظاهرة وتفسيرها في تحليل الاستمارة، أما العينة، فقد طبقنا في دراستنا هذه العينة الطبقية النسبية، والتي تمثل عدد أفرادها في 105 مفردات قمنا بتوزيع الاستمارة عليهم، بينما تم استرداد 95 من المجموع الموزع. خلصت نتائج الدراسة إلى أن للاتصال الرسمي دور كبير في تحفيز العاملين في هذه المؤسسة، إذ يدفعهم إلى أداء مهام أفضل، ويتيح لهم التعبير عن اهتماماتهم وانشغالاتهم من خلال الاستماع إليهم والمشاركة في صنع القرار، بالإضافة إلى الاهتمام بالعامل من الناحية الأخلاقية في توجيهه وتطويره. إن تنمية قدراته ومهاراته وخلق شعور بالانتماء لمؤسسته، كل ذلك من شأنه أن يؤدي إلى تحقيق أهداف المؤسسة.
Keywords: الاتصال الرسمي، تحفيز، المورد البشري